Coastal applications from nadir altimetry: Example of the X-TRACK regional products. Issue 4 (15th February 2017) - Birol, F.; Fuller, N.; Lyard, F.; Cancet, M.; Niño, F.; Delebecque, C.; Fleury, S.; Toublanc, F.; Melet, A.; Saraceno, M.; Léger, F.
Abstract: In the coastal ocean zones, satellite altimetry data processing and interpretation poses specific difficulties, due to the interaction of the radar signal with land topography, inaccuracies in some of the geophysical corrections and to the fast changes in the sea level. In order to optimize the completeness and the accuracy of the sea surface height information derived from satellite altimetry in coastal ocean areas, a dedicated post-processing software, called X-TRACK, has been developed by the Center of Topography of the Ocean and Hydrosphere in Toulouse. It is tailored for extending the use of altimetry data to coastal ocean applications and provides freely available along-track Sea Level Anomaly time series that cover today all the coastal oceans. Here, we present the improvements made in version 2016 of X-TRACK and show the gain in near-coastal data accuracy using in situ tide gauge observations. The correlations between altimeter and tide gauge sea level anomalies are higher (by 15% in average) compared with the previous version of X-TRACK. Three examples of applications are shown. The recent evolutions done in the X-TRACK processing result in an improved observation of the seasonal variations of the boundary circulation in the Bay of Biscay. Along Western Africa, sea-level variations derived from X-TRACK data are observed closer to land (5 km) compared to AVISO (10 km), and the sea-level statistics are more robust due to the larger and more stable data availability. Along-track empirical tidal constants derived from X-TRACK Sea Level Anomaly time series are also used to validate tidal models. By improving the altimetric data accuracy in coastal areas, we extend the field of marine applications.